Rapid nanobody-based imaging of mesothelin expressing malignancies compatible with blocking therapeutic antibodies - Benloucif, Abdennour; Meyer, Damien; Balasse, Laure; Goubard, Armelle; Danner, Lucile; Bouhlel, Ahlem; Castellano, Rémy; Guillet, Benjamin; Chames, Patrick; Kerfelec, Brigitte (Frontiers in Immunology, 2023)
Mesothelin (MSLN), overexpressed in a wide variety of cancers with few therapeutic options, has recently emerged as an attractive target for cancer therapy and a large panel of approaches are currently under preclinical and clinical investigations. In this respect, developing mesothelin specific tracers as molecular companion tools for predicting the patient eligibility, monitoring the response to mesothelin-targeting therapies and the evolution of the disease or for real-time visualization of tumors during surgery is of growing importance. We generated by phage display a nanobody (Nb S1) that displays a high apparent affinity and specificity for human mesothelin and demonstrated that its binding, although located in the membrane distal domain of mesothelin is not impeded by the presence of MUC16, the only known ligand of mesothelin, nor by the therapeutic antibody amatuximab. Enzymatic approaches were used to site-directed conjugate Nb S1 with either ATTO 647N fluorochrome or NODAGA chelator for fluorescence and positron emission tomography imaging (PET) respectively. In vivo experiments showed that both ATTO 647N-and [68Ga]NODAGA-Nb S1 rapidly and specifically accumulated in mesothelin positive tumors compared to mesothelin negative tumor or irrelevant Nb with a high tumor/background ratio. As well, ex vivo biodistribution profile analysis confirmed a significant higher uptake of Nb S1 in MSLN-positive tumors than in MSLNlow tumors. We demonstrated for the first time the use of an anti-MSLN nanobody as PET radiotracer for same day imaging of MSLN+ tumors, targeting an epitope compatible with the monitoring of amatuximab-based therapies and current SS1-derived-drug conjugates.